Problematics in Postmodernism: An Opportunity and Challenge in Discourse of Prophetic Sociology Method - Peribadi, Peribadi; Samsul, Samsul (UIN Maulana Malik Ibrahim Malang, 2019)
Almost all aspects of the social life of this beloved nation and country tended to be colonized including for the academicians that up to now have still been subduing and been kneeling under the influence of western epistemology. Therefore, in the case of obtaining the independence of thinking academically to develop the charitable science and scientific charity, it needs the paradigm and alternative epistemology according to the socio-psychological and socio-anthropological of the nation. In addition to the urgent independence demand for thinking academically, it also still opened the opportunity to develop a prophetic based methodology discourse. There is still an empty space in the context of methodological compilation enabling a new methodology emerges in the future. As the first step to construct a prophetic paradigm is formulating the philosophical foundation in the context of ontology, epistemology, and axiology in social science. This paper offered several strategic phases towards the discourse of metaphysical realism to develop alternative methodologies within the circle of postmodernism problematics. Hampir semua aspek kehidupan sosial bangsa dan negara tercinta ini cenderung dijajah termasuk para akademisi yang sampai sekarang masih tunduk dan berlutut di bawah pengaruh epistemologi barat. Oleh karena itu, dalam hal memperoleh kemandirian berpikir secara akademis untuk mengembangkan ilmu amal dan amal ilmiah, diperlukan paradigma dan epistemologi alternatif sesuai dengan sosio-psikologis dan sosio-antropologis bangsa. Selain tuntutan kemandirian yang mendesak untuk berpikir secara akademis, masih terbuka peluang untuk mengembangkan wacana metodologi berbasis kenabian. Masih ada ruang kosong dalam konteks kompilasi metodologis yang memungkinkan metodologi baru muncul di masa depan. Sebagai langkah pertama untuk membangun paradigma profetik adalah merumuskan landasan filosofis dalam konteks ontologi, epistemologi, dan aksiologi dalam ilmu sosial. Makalah ini menawarkan beberapa fase strategis menuju wacana realisme metafisik untuk mengembangkan metodologi alternatif dalam lingkaran problematika postmodernisme.